2020
DOI: 10.1021/acs.jafc.0c01250
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid–Protein Structured Membrane for Microencapsulation of DHA Oil and Evaluation of Its In Vitro Digestibility: Inspired by Milk Fat Globule Membrane

Abstract: The present study aims to design a milk fat globule membrane (MFGM)-inspired structured membrane (phospholipid- and protein-rich) for microencapsulation of docosahexaenoic acid (DHA) oil. DHA-enriched oil emulsions were prepared using different ratios of sunflower phospholipid (SPL), proteins [whey protein concentrate (WPC), soy protein isolate (SPI), and sodium caseinate (SC)], and maltodextrin and spray-dried to obtain DHA microcapsules. The prepared DHA oil emulsions have nanosized particles. SPLs were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The LDs of human milk and the O/W emulsion in the intestinal phase are consistent. Compared to IF, human milk and the O/W emulsion exhibited higher LDs at the end of intestinal digestion, which could be attributed to the structured PL-protein at the interface . And the LDs were 68.00 ± 1.05% for human milk, 62.74 ± 2.51% for the O/W emulsion, and 50.90 ± 2.70% for IF.…”
Section: Resultsmentioning
confidence: 99%
“…The LDs of human milk and the O/W emulsion in the intestinal phase are consistent. Compared to IF, human milk and the O/W emulsion exhibited higher LDs at the end of intestinal digestion, which could be attributed to the structured PL-protein at the interface . And the LDs were 68.00 ± 1.05% for human milk, 62.74 ± 2.51% for the O/W emulsion, and 50.90 ± 2.70% for IF.…”
Section: Resultsmentioning
confidence: 99%
“…The authors thus suggested that the SL molecules gradually replaced the interfacial proteins and that the displaced interfacial proteins subsequently self-aggregated. The charged groups became masked through aggregation, resulting in a reduction in the absolute value of the ζpotential of the emulsion (Kwaambwa and Rennie, 2012;Chen et al 2020).…”
Section: Physical Stability Of the Sifesmentioning
confidence: 99%
“…These changes reflect changes in the interor intramolecular forces between amino acids in the protein and surrounding mediators (Miranda, 2001;Gu et al 2010). Chen et al (2020) reported that shifts in the bands of amides I and II indicated that the addition of sunflower phospholipid effectively enhanced the hydrogen-bonding forces of whey protein concentrate, sodium caseinate and soy protein isolate, thereby improving protein stability. Therefore, based on the changes in the vibrations of its functional groups, SL may also generate a force that affects the protein structure, which is consistent with our results.…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…With the extension of storage period, the quality of emulsion changed gradually, with continuous increase in particle size (Young and Nitin, 2019). In general, the system is considered to be relatively stable when the zeta-potential reaches 25 mV in absolute value (Chen et al, 2020). Figure 6C demonstrates that the zeta-potential values increased with the increase of storage days, and the absolute value was above 25 mV at 5°C and 25°C during storage days, which depicted that AST nanoemulsions prepared by LYCRPLs could be stable for 28 days at 5°C and 25°C, and became slightly unstable at higher temperature.…”
Section: Storage Stability Of Ast Nanoemulsionsmentioning
confidence: 99%